2021
DOI: 10.29219/fnr.v65.4998
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects of the soluble dietary fiber from tartary buckwheat bran in diabetic mice and their potential mechanisms

Abstract: Background: Tartary buckwheat has beneficial effects on glucose and lipid metabolism of patients with type 2 diabetes mellitus. However, the physiological effects of a soluble dietary fiber (SDF) from tartary buckwheat have rarely been studied, especially in vivo. Objective: This study aimed to examine the hypoglycemic and hypolipidemic effects of SDF from tartary buckwheat bran on high-fat diet/streptozotocin-induced diabetic mice. Design: The SDF of tartary buckwheat bran was collected according to the Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…With the increase of TBBF, the TDF contents ranged from 3.47 to 9.92 g per 100 g, the IDF contents ranged from 2.55 to 8.48 g per 100 g, and the SDF contents ranged from 0.7 to 1.37 g per 100 g. The increase of dietary fiber in TBDNs was related to the higher dietary fiber content of Tartary buckwheat bran compared to Tartary buckwheat flour [ 36 ]. In addition, the dietary fiber of Tartary buckwheat bran was dominated by insoluble dietary fiber [ 37 ]. Combined with the results for quality, although the addition of TBBF weakened the tenacity of the TBDNs, there was little change in the hardness and resilience, and the bioactive compound (phenolic, flavonoids and dietary fiber) content of the TBDNs was increased significantly ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of TBBF, the TDF contents ranged from 3.47 to 9.92 g per 100 g, the IDF contents ranged from 2.55 to 8.48 g per 100 g, and the SDF contents ranged from 0.7 to 1.37 g per 100 g. The increase of dietary fiber in TBDNs was related to the higher dietary fiber content of Tartary buckwheat bran compared to Tartary buckwheat flour [ 36 ]. In addition, the dietary fiber of Tartary buckwheat bran was dominated by insoluble dietary fiber [ 37 ]. Combined with the results for quality, although the addition of TBBF weakened the tenacity of the TBDNs, there was little change in the hardness and resilience, and the bioactive compound (phenolic, flavonoids and dietary fiber) content of the TBDNs was increased significantly ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies applied Tartary buckwheat and reported differences in the animal fecal microbiome in comparison to a high-fat diet [ 7 , 34 , 44 , 45 , 46 , 48 , 49 , 50 ] and basal diet [ 53 ]. In Supplemental Figure S2 , we summarized the findings on differences in GI microbiota from animal studies using Tartary buckwheat as an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Tartary buckwheat powder supplementation had no effect on the fecal SCFAs concentration. Wu et al [ 48 ] studied the antidiabetic effect of the soluble dietary fibers from Tartary buckwheat brans using mice with induced diabetes by feeding with a high-fat diet for five weeks. The diabetic groups were then given a varying (low, moderate, and high) dose of buckwheat fibers for eight weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the polysaccharide fraction displayed α-glucosidase inhibitory activity. Wu et al [ 44 ] found that the SDF of Tartary buckwheat bran improved glucose and lipid metabolism in diabetic mice. Next to carbohydrates, proteins are the most abundant macronutrient of Tartary buckwheat bran.…”
Section: Nutritional Compounds Of Tartary Buckwheat Branmentioning
confidence: 99%